Understanding Phrases in Forming Sentences - Andini, Aula; Nurhalizah, Diva; Azhar Pane, Fahmi; Anwar, Khoirul; Lubis, Yani (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
Phrases are fundamental to constructing cohesive sentences and conveying meaning in language. This study explores the theoretical and practical applications of phrases in language teaching, combining insights from linguistic frameworks and modern pedagogical practices. Participants across varying proficiency levels engaged in structured phrase-based learning activities delivered through traditional and technology-enhanced methods. The findings demonstrate that phrase-focused instruction significantly improves syntactic accuracy, semantic clarity, and communicative competence. Additionally, the integration of multimedia tools enhances learner engagement and reinforces learning outcomes. This research highlights the dual role of phrases as structural and functional elements in language, underscoring their importance in both theoretical linguistics and practical pedagogy. By bridging traditional methodologies with interactive technologies, the study offers a comprehensive framework for advancing language education. These findings provide valuable insights into innovative teaching strategies and emphasize the pivotal role of phrases in fostering effective communication.